Role of the Cytoskeleton in Steroidogenesis - Wu, Zaichao; Zhang, Chunping (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Steroidogenesis in the adrenal cortex or gonads is a complicated process modulated by various elements either at the tissue or molecular level. The substrate cholesterol is first delivered to the outer membrane of mitochondria, undergoing a series of enzymatic reactions along with the material exchange between the mitochondria and the ER (endoplasmic reticulum) and ultimately yielding various steroids, such as aldosterone, cortisol, testosterone, and estrone. Several valves are set to adjust the amount of production as per the needs, e.g., StAR (steroidogenic acute regulator) controls the traffic of cholesterol from the outer membrane to the inner membrane of mitochondria which is a rate-limiting step. Moreover, the “need” is partly reflected by trophic signals, like ACTH, LH, and downstream pathways, such as the intracellular cAMP pathway, representing the endocrinal regulation of steroid synthesis. The coordinated activities of these related factors are all associated with another crucial cellular constituent, the cytoskeleton, which plays a crucial role in cellular architecture and substrate trafficking. Though considerable studies have been performed regarding steroid synthesis, details regarding the upstream signaling pathways and mechanisms of the regulation by the cytoskeleton network still remain unclear. The metabolism and interplays of the pivotal cellular organelles with cytoskeleton are worth exploring as well. This review summarizes the research of different periods, describing the roles of specific cytoskeleton elements in steroidogenesis and related signaling pathways involved in steroid synthesis. In addition, we discuss the inner cytoskeletal network involved in steroidogenic processes, such as mitochondrial movement, organelle interactions, and cholesterol trafficking.
Keywords: Cholesterol